KEARIFAN LOKAL MASYARAKAT DALAM MELESTARIKAN TRADISI HOYAK TABUIK DI KOTA PARIAMAN SUMATERA BARAT - Awan Hadijah; Gabriella Afriza Ayu; Syamsir (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
Local wisdom is a way of life, or it can be interpreted as a culture, which is inherent and developing in the local community and can be passed down from generation to generation in the form of an activity. The Hoyak Tabuik tradition is a ceremony to commemorate the death of Saidina Imam Husein, the grandson of the Prophet Muhammad (Saidina Imam Husein), and is carried out by the Pariaman people every 10th of the Hijri calendar by turning Tabuik into a human head and the carcass of a 'Buraq bird'. This study aims to find out the description of the hoyak tabuik tradition and find the cultural and religious values ​​that are transmitted in the hoyak tabuik traditions and rituals. In this study, researchers used a qualitative description method. And the interview method has been used to access various sources when collecting research data. The results of this study explain how the hoyak tabuik tradition exists in the city of Pariaman and the cultural values ​​that we can take from this tradition, namely the values ​​of friendship and mutual cooperation, as well as religious values, namely the expression of gratitude.